The CYP1B1 gene mutation prevalence in primary congenital glaucoma: A review of Pakistani families - Arshad, Asma; Laraib, Fiza; Bibi, Sana; Arshad, Muhammad Usman; Arshad, Sana (International Journal of Applied and Experimental Biology, 2026)
Glaucoma is the second leading cause of blindness worldwide. It is a neuropathic disease, mostly inherited in an autosomal recessive form. Primary congenital glaucoma (PGC) is characterized by increased intraocular pressure and optic nerve damage. It is a clinically and genetically heterogeneous eye disorder. To date, four genetic loci are reported to have been linked to PCG, including GLC3A, GLC3B, GLC3C, and GLC3D. The CYP1B1 gene resides in the GLC3A locus on chromosome 2. Mutations in the CYP1B1 gene are linked to PCG. It is most prevalent in countries like Pakistan, where consanguinity is common. Both familial and sporadic forms of PCG are common in Pakistan. This study was undertaken to analyze the mutations in the CYP1B1 gene in the cause of PCG in consanguineous Pakistani families. The CYP1B1 mutations linked to PCG in consanguineous Pakistani families were analyzed from a thorough analysis of the data available to date on Google Scholar, Medline, and PubMed, and were further demonstrated by a pie-chart diagram. The graphical representation of the percent prevalence of these mutations was accessed. A total of 98 missense, frameshift, and nonsense mutations were found. The missense mutation, p.Arg390His, was the most significant, particularly in Punjab, followed by the p.Glu229Lys mutation. In Pakistan, there is a higher prevalence of PCG in consanguineous families. Several mutations in the CYP1B1 gene cause PCG in the Pakistani population, with p.Arg390His being the dominant one. Knowledge of prevalent PCG-causing mutations in a population is useful in establishing prenatal and pre-symptomatic diagnoses for better glaucoma management.